Investigating the modulatory effects of Moringa oleifera on the gut microbiota of chicken model through metagenomic approach - Soundararajan, Sowmiya; Selvakumar, Jasmine; Maria Joseph, Zion Mercy; Gopinath, Yuvapriya; Saravanan, Vaishali; Santhanam, Rameshkumar (Frontiers in Veterinary Science, 2023)
Introduction This study aimed to assess the effects of supplementing chicken feed with Moringa oleifera leaf powder, a phytobiotic, on the gastrointestinal microbiota. The objective was to examine the microbial changes induced by the supplementation. Methods A total of 40, one-day-old chickens were fed their basal diet for 42 days and then divided into two groups: SG1 (basal diet) and SG2 (basal diet + 10 g/kg Moringa oleifera leaf powder). Metagenomics analysis was conducted to analyze operational taxonomic units (OTUs), species annotation, and biodiversity. Additionally, 16S rRNA sequencing was performed for molecular characterization of isolated gut bacteria, identified as Enterococcus faecium. The isolated bacteria were tested for essential metabolites, demonstrating antibacterial, antioxidant, and anticancer activities. Results and discussion The analysis revealed variations in the microbial composition between the control group (SG1) and the M. oleifera-treated group (SG2). SG2 showed a 47% increase in Bacteroides and a 30% decrease in Firmicutes, Proteobacteria, Actinobacteria, and Tenericutes compared to SG1. TM7 bacteria were observed exclusively in the M. oleifera-treated group. These findings suggest that Moringa oleifera leaf powder acts as a modulator that enhances chicken gut microbiota, promoting the colonization of beneficial bacteria. PICRUSt analysis supported these findings, showing increased carbohydrate and lipid metabolism in the M.oleifera-treated gut microbiota. Conclusion This study indicates that supplementing chicken feed with Moringa oleifera leaf powder as a phytobiotic enhances the gut microbiota in chicken models, potentially improving overall health. The observed changes in bacterial composition, increased presence of Bacteroides, and exclusive presence of TM7 bacteria suggest a positive modulation of microbial balance. The essential metabolites from isolated Enterococcus faecium bacteria further support the potential benefits of Moringa oleifera supplementation.